Prevalence of vitamin D insufficiency and deficiency in Mexican adults with allergic asthma - Martín Bedolla-Barajas; Juan Carlos López-Hernández; Lourdes Fabiola García-Padilla; Jaime Morales-Romero; Fernando Antonio Velarde-Rivera; Martín Robles-Figueroa; José Raúl Ortiz-Peregrina (Revista Alergia México, 2017)
Background: Hypovitaminosis D has been associated with various chronic diseases such as infections, autoimmune diseases, chronic obstructive pulmonary disease, cancer and asthma